Penerapan Akuntansi Manajemen Dalam Pengendalian Biaya Operasional Tambang - Hana Anastasya Li Zebua (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study aims to analyze the implementation of management accounting in controlling operational costs in mining companies. The mining industry is characterized by large and complex cost structures, requiring an effective cost control system. This research employs a descriptive qualitative approach supported by quantitative data. Data were collected through interviews, observations, and documentation of operational cost reports and company budgets. The results indicate that management accounting has been implemented through budgeting, cost recording based on responsibility centers, and periodic cost reporting. However, unfavorable cost variances were still found in several major cost components, particularly fuel and equipment maintenance costs. This finding suggests that although the management accounting system has been implemented, the effectiveness of cost control needs further improvement, especially in variance analysis and managerial follow-up. This study is expected to contribute to the development of management accounting and serve as a reference for mining company management in improving operational cost efficiency.